The management team handbook five key strategies for maximizing group performance - McIntyre, Marie G. 1947- (San Francisco, California Jossey-Bass Publishers, 1998)
Based on research involving more than seventy management teams and on the author's own extensive team-consulting experience, this book outlines five success factors proven to optimize the performance of management teams in business, government, and nonprofit organizations. Including a flexible team model, assessment survey, compelling case studies, and other results-oriented tools, The Management Team Handbook is a one-of-a-kind guide to creating and maintaining the most dynamic management teams possible.
Introduction: The Challenge of Developing a Management Team -- Creating a Leadership Team -- Five Key Strategies for Management Team Success -- Strategic Goals: How to Establish Direction for Your Organization -- Extensive Networks: How to Connect with Sources of Information -- Collaborative Relationships: How to Develop Cooperation Among Departments -- Effective Information Processing: How to Make Good Group Decisions -- Focused Action: How to Move from Discussion to Results -- Management Team Maintenance -- Keeping the Team Productive -- Selecting New Team Members -- Managing Team Transitions -- Fixing a Sick Team -- Conclusion: Twelve Guiding Principles for High Performance.
Includes bibliographical references (pages 251-252) and index.
Keywords: Teams in the workplace; Executives